The Marri Gudjaga project: a study protocol for a randomised control trial using Aboriginal peer support workers to promote breastfeeding of Aboriginal babies - Rebecca Thorne; Rowena Ivers; Michelle Dickson; Karen Charlton; Lisa Jackson Pulver; Christine Catling; Michael Dibley; Simon Eckermann; Shahla Meedya; Miranda Buck; Patrick Kelly; Elizabeth Best; et al. (BMC, 2023)
Background Breastfeeding protects against a range of conditions in the infant, including sudden infant death syndrome (SIDS), diarrhoea, respiratory infections and middle ear infections [1, 2]. The World Health Organization (WHO) recommends exclusive breastfeeding until six months of age, with continued breastfeeding recommended for at least two years and other complementary nutritious foods [3]. The 2017-18 National Health Survey (NHS) and 2018-19 National Aboriginal and Torres Strait Islander Health Survey (NATSIHS) reported that the proportion of breastfeeding in Aboriginal and Torres Strait Islander infants (0-2 years) were less than half that of non-Indigenous infants (21.2% vs. 45%, respectively)[4]. There is a lack of research on interventions supporting Aboriginal women to breastfeed, identifying an evaluation gap related to peer support interventions to encourage exclusive breastfeeding in Aboriginal women. Methods We will evaluate the effect of scheduled breastfeeding peer support for and by Aboriginal women, on breastfeeding initiation and the prevalence of exclusive breastfeeding. This MRFF (Medical Research Future Fund) funded project is designed as a single-blinded cluster randomised controlled trial recruiting six sites across New South Wales, Australia, with three sites being randomised to employ a peer support worker or undertaking standard care. Forty pregnant women will be recruited each year from each of the six sites and will be surveyed during pregnancy, at six weeks, four and six months postnatally with a single text message at 12 months to ascertain breastfeeding rates. In-depth interviews via an Indigenous style of conversation and storytelling called 'Yarning' will be completed at pre- and post-intervention with five randomly recruited community members and five health professionals at each site" [5]. Yarns will be audio recorded, transcribed, coded and thematic analysis undertaken. Health economic analysis will be completed to assess the health system incremental cost and effects of the breastfeeding intervention relative to usual care. Discussion Evidence will be given on the effectiveness of Aboriginal peer support workers to promote the initiation and continuation of breastfeeding of Aboriginal babies. The findings of this study will provide evidence of effectiveness and cost-effectiveness of including peer support workers in postnatal care to promote breastfeeding practices. Trial Registration ACTRN12622001208796 The impact of breastfeeding peer support on nutrition of Aboriginal infants